2005
DOI: 10.1002/eji.200425883
|View full text |Cite
|
Sign up to set email alerts
|

Integrin activation by bacterial fimbriae through a pathway involving CD14, Toll‐like receptor 2, and phosphatidylinositol‐3‐kinase

Abstract: CD11b–CD18 and other integrins play important roles in immunity and inflammation and require prior activation through inside‐out signaling to efficiently bind their ligands. We present evidence for a novel TLR2‐dependent signaling pathway that leads to CD11b–CD18 activation in human monocytes or neutrophils upon recognition of Porphyromonas gingivalis fimbriae through CD14. The activated binding‐state of CD11b–CD18, which involves induction of conformational changes, was monitored through detection of an activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 107 publications
(178 citation statements)
references
References 39 publications
6
171
0
1
Order By: Relevance
“…CR3 exploitation by P. gingivalis is initiated at the level of TLR2, since TLR2 inside-out signaling is required for effective interaction of P. gingivalis fimbriae with CR3 (Harokopakis et al, 2006;Harokopakis and Hajishengallis, 2005). Consistent with this, we have now found that the intracellular survival of fimbriated P. gingivalis is dramatically reduced in TLR2-deficient macrophages relative to normal controls (Fig.…”
Section: Cr3 Exploitation By P Gingivalis Depends On Tlr2supporting
confidence: 80%
See 1 more Smart Citation
“…CR3 exploitation by P. gingivalis is initiated at the level of TLR2, since TLR2 inside-out signaling is required for effective interaction of P. gingivalis fimbriae with CR3 (Harokopakis et al, 2006;Harokopakis and Hajishengallis, 2005). Consistent with this, we have now found that the intracellular survival of fimbriated P. gingivalis is dramatically reduced in TLR2-deficient macrophages relative to normal controls (Fig.…”
Section: Cr3 Exploitation By P Gingivalis Depends On Tlr2supporting
confidence: 80%
“…Rather, CR3 engages in cooperative interactions with the CD14/TLR2 signaling complex in response to P. gingivalis fimbriae. Hajishengallis et al, 2006a;Hajishengallis et al, 2006b;Harokopakis and Hajishengallis, 2005). According to this model, P. gingivalis fimbriae bind CD14 and activate TLR2-and phosphatidylinositol 3-kinase (PI3K)-mediated inside-out signaling leading to activation of the ligand-binding capacity of CR3 (Fig.…”
Section: P Gingivalis Interacts With Crthrough Its Cell Surface Fimbmentioning
confidence: 99%
“…It has been shown that TLR2 and CD14 play a crucial role in recognition of FimA by monocytes (6,9). Moreover, membrane-expressed CD14 is an essential coreceptor for TLR2-mediated cell activation by P. gingivalis FimA (6).…”
Section: Resultsmentioning
confidence: 99%
“…Cell culture supernatants were then separated by centrifugation and stored at Ϫ80°C prior to a cytokine protein assay by use of Luminex 100 technology using a multiplex for four cytokines: IL-6, IL-8, GM-CSF, and TNF-␣ (Upstate Cell Signaling Solutions, NY). Human monocytes (1.5 ϫ 10 5 /well) were stimulated as described previously (9). Briefly, monocytes were incubated at 37°C under 5% CO 2 with heat-killed P. gingivalis (MOI, 100:1), Pam3Cys and FSL-1, (both at 1 g/ml), and FimA (1 or 10 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of gram-positive bacterial components, evidence suggests that CD14 can enhance TLR2-dependent signaling in macrophages (Harokopakis and Hajishengallis, 2005;Manukyan et al, 2005;Schroder et al, 2003). The majority of Toll-like receptors identified to date utilize a common signal transduction pathway with minor differences that appear to confer specificity in response to distinct ligands (Akira and Hemmi, 2003;Gantner et al, 2003;Takeda et al, 2003).…”
Section: Modulation Of Cd14 Ko Microglial Activation In Response To Bmentioning
confidence: 99%